2014
DOI: 10.4161/bact.28365
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs in bacteriophage life histories

Abstract: Viruses are the most abundant biological entities on the planet, yet most classical principles of evolutionary biology and ecology were not developed with viruses in mind. Here, the concept of biological tradeoffs, a fundamental tenet of life history theory, is examined in the context of bacteriophage biology. Specifically, several important parameters of phage life histories-replication, persistence, host range, and adsorption-are evaluated for tradeoffs. Available data indicate that replication rate is stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…It was recently reported that a generalist EhV strain could outcompete a specialist 8 h post infection [92]. One explanation for this apparent difference in infective success between generalist and specialist viruses may thus be a trade-off where high host-range/replication rates are associated with hindered progeny (new virions) fitness [64,93,94,95,96]. An alternative possibility could be the presence of an “un-costly” strong adaptive potential to new hosts, as shown for the Tobacco etch potyvirus (TEV) [97].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that a generalist EhV strain could outcompete a specialist 8 h post infection [92]. One explanation for this apparent difference in infective success between generalist and specialist viruses may thus be a trade-off where high host-range/replication rates are associated with hindered progeny (new virions) fitness [64,93,94,95,96]. An alternative possibility could be the presence of an “un-costly” strong adaptive potential to new hosts, as shown for the Tobacco etch potyvirus (TEV) [97].…”
Section: Discussionmentioning
confidence: 99%
“…As was the case for virus multiplication in susceptible hosts (25), the sense and magnitude of the pleiotropy depend on the specific mutations that determine resistance breaking and not on the pathotype. Hence, there is no trade-off in this system between increased host range (i.e., resistance breaking) and survival, as has been reported for bacteriophages (55,58). Also, the analysis of the within-host fitness of these coat protein mutants (Table 2) shows that fitness and particle stability rank differently.…”
Section: Discussionmentioning
confidence: 84%
“…This result is consistent with previous ones, as data on the within-host fitness of some of the CP mutants analyzed here, reported by MorenoPérez et al (25), showed no correlation with our present stability data in different susceptible hosts (not shown). To our knowledge, the relationship between survival and multiplication has not been studied for other plant viruses, but studies with bacterial or animal-infecting viruses have demonstrated that such a trade-off is not general across systems (55)(56)(57)(58)(67)(68)(69)(70)(71)(72). Trade-offs between survival and reproduction, predicted by the life history theory, need not apply for viruses, because there is no obvious mechanistic reason to expect them due to the differences between the extracellular and intracellular environments where survival and reproduction, respectively, occur, as pointed out by Goldhill and Turner (19).…”
Section: Discussionmentioning
confidence: 99%
“…Some mutant phages increase their infectivity by improving their adsorption efficiency (18,(32)(33)(34). The adsorption efficiencies of the KPP22 mutant phages were compared with that of phage KPP22 (Fig.…”
Section: Resultsmentioning
confidence: 99%